Economic and Social Development along the Urban-Rural Continuum : New Opportunities to Inform Policy - Cattaneo, Andrea; Adukia, Anjali; Brown, David L.; Christiaensen, Luc; Evans, David K.; Haakenstad, Annie; McMenomy, Theresa; Partridge, Mark; Vaz, Sara; Weiss, Daniel J. (World Bank, Washington, DC, 2021)
The economic and social development of nations relies on their population having physical access to services and employment opportunities. For the vast majority of the 3.4 billion people living in rural locations, this largely depends on their access to urban centers of different sizes. Similarly, urban centers depend on their rural hinterlands. Building on the literature on functional areas/territories and the rural-urban continuum as well as insights from central place theory, this review paper advances the notion of catchment areas differentiated along an urban-to-rural continuum to capture these urban-rural interconnections. It further shows how a new, publicly available data set operationalizing this concept can shed new light on policy making across a series of development fields, including institutions and governance, urbanization and food systems, welfare and poverty, and access to health and education services. Together the insights support a more geographically nuanced perspective on development.